Protection of Victims of The Crime of Rape Reviewed from Law and Human Rights - Herawan Rafiq Nugroho; Taufiq Nugroho (Proceeding International Conference Restructuring and Transforming Law, 2023)
Rape is an act of forcing sexual intercourse in any form against one's will or against one's will. This form of crime knows no gender, age, socioeconomic status, place, and time. Commitment and firmness in upholding human rights and guaranteeing that all citizens have equal standing before the law. Rape victims do receive attention, but often the attention given by human rights defenders is only partial, not optimal and is only used as an object of research. Legal protection is the most important thing in the elements of a rule of law, because legal protection is the right of every citizen and the obligation of the state as the organizer of protection. Normative juridical research methods, how to analyze library materials, namely primary and secondary legal materials. That humans must get protection from things that take away human rights in life, so women's human rights must be protected, respected, maintained, and cannot be ignored, reduced, or seized by anyone. It is a fact that acts of violence against women are a constant threat to women anywhere in the world and acts of violence against women have become a global issue. Law enforcement officials must simultaneously respect justice and human rights, although the balance between respect for truth and justice and respect for and uphold human rights values in resolving criminal incidents is very difficult to define. However, this difficulty should not become a narrow and rigid technical reason in giving the perpetrators of criminal acts freedom to freely move around in society.